PENGARUH JENIS BUSI TERHADAP KONSUMSI BAHAN BAKAR MOTOR BAKAR 4 TAK - TINUS GINTING (STMIK KAPUTAMA, 2021)
The purpose of this study was to determine how much influence the use of standard, platinum, and iridium spark plugs on fuel consumption on motorcycles supra x 125. The method used in this study is an experimental method or direct experiment. Turn on the motorbike, then increase the engine speed according to the design. Use a tachometer to measure the rpm whether it is in accordance with that set in the study. Use a stop watch to calculate the test time and after finishing see the results that have been obtained. By doing the no-load test 3 times in each experiment that you want to test. The results show that using platinum and iridium spark plugs can reduce fuel consumption.